Treatment of corneal neovascularization with dietary isoflavonoids and vlavonoids - Joussen, Antonia J. M.; Rohrschneider, Klaus; Reichling, Jürgen; Kirchhof, Bernd; Kruse, Friedrich E. (Experimental eye research, 2000)
The purpose of this study was to investigate the use of dietary isoflavonoids and flavonoids for the treatment of ocular neovascularization. Corneal blood vessels were induced by intrastromal implantation of pellets containing bFGF. Isoflavonoids and flavonoids (Genistein, Fisetin and Luteolin) were dissolved in a microemulsion to increase bioavailability and applied topically in concentrations between 0.5 and 1ng ml−1. Corneal neovascularization was quantified under the microscope. In comparison to control eyes, all three substances significantly inhibited corneal neovascularization (P⩽0.05). Fisetin had the strongest effect followed by Genistein and Luteolin. No significant topical side effects were observed. We concluded that the isoflavonoid Genistein and two structurally related flavonoids are potent inhibitors of corneal angiogenesis in vivo. The wide distribution of the flavonoids in the plant kingdom together with the presented results suggests that flavonoids may contribute to the preventive effect of a plant-based diet on neovascular disease of the eye.
Gesehen am 03.03.2021